Storage Constrained Linear Computation Coding - Karataev, Alexander; Rosenberger, Hans; Bereyhi, Ali; Müller, Ralf (Data Compression Conference Proceedings, 2023)
Linear computation coding (LCC) has been developed in [1] as a new framework for the computation of linear functions. LCC significantly reduces the complexity of matrix-vector multiplication [1]. In basic LCC, storage is not restricted i.e. the wiring exponents are arbitrary integer exponents of 2.
CRIS-Team Scopus Importer:2023-06-09
Keywords: approximate computing; computational complexity; fixed point arithmetic; function compression; linear systems; quantization